Pharmacotherapy for diabetic retinopathy : it is not just a dream - Kaštelan, Snježana (Array, 2008)
Summary: Diabetic retinopathy is a major cause of new blindness among working-age individuals in developed countries and remains one of the most serious complications of diabetes. At the time, primary prevention with intensive glycemic control, strict blood pressure regulation and lipid-modifying therapy, as well as local ocular treatment (laser photocoagulation and pars plana vitrectomy) are the proven standard treatments for diabetic retinopathy. However, more recently, many researchers have directed their efforts towards better understanding of microvascular changes in diabetic retinopathy in order to develop more effective pharmacologic prevention and treatment, and to determine new treatment strategies. The three major classes of agents currently being studied are corticosteroids, vascular endothelial growth factor (VEGF) antagonists and agents that are involved in biochemical pathways (polyol activation, and changes in macromolecule structure and function via the formation of AGE products). As further prospective randomized clinical trials accumulate data, the role and guidelines of pharmacologic treatments will become clearer